Kajian Komposisi Pupuk NPK terhadap Pola Pertumbuhan dan Perkembangan Fase Generatif Labu Madu Hibrida - Nasihin, Muhammad Hoirul; ., Mawardi (JURNAL AGROPLANT, 2023)
This research is a qualitative descriptive research carried out at the Experimental Garden in Pancakarya Village, Ajung District, Jember Regency with a height ranging from 50 meters above sea level. To describe and find out the facts or events that will be examined or research conducted to make it easier for researchers to obtain objective data. This research used 27 honey gourd plants cultivated by Siti Masruroh's sister. Observations were made from June to August 2022. Observations were made using variables that were analyzed descriptively, namely: the number of branching, the appearance of male and female flowers, the presence of flowers and fruits in the plant structure, the percentage of flowers turning into fruit, the percentage of fruit until harvest. Observations were made when the honey gourd plants entered the generative phase, around 18 days after planting until harvest. Supporting observations were carried out on types of pests and diseases, as well as pearl NPK fertilizer analysis. The results of the study stated that the composition of NPK 1:2:3 (K3) had a good effect on the number of branches, the appearance of male and female flowers, the presence of fruit in plant structure, and the percentage of flowers turning into fruit. And the pattern of generative growth of honey gourd with various compositions of NPK fertilizer produces optimal results and is in line with the success of vegetative propagation of honey gourd seedlings.